A STUDY OF PBL-BASED LEARNING FOR INCREASING STUDENT’S CRITICAL THINKING SKILLS AT STATE MADRASAH ALIYAH - Destianti, Alfika; Antoni, Rizal (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This research is motivated by the ability of students to understand and apply the concept of static fluid. This study aimed to describe the PBL, improve critical thinking skills, and describe the increased ability to understand the concept of static fluid in class nine students at MAN2 Indragiri Hilir with the application of PBL. This study uses a descriptive qualitative approach to the type of Classroom Action Research. The action given was in the form of applying a PBL, carried out in two cycles. The activities of each cycle include planning, action, observation, and reflection. The subjects in the study were class nine students at the MAN 2 Indragiri Hilir, with a total of 13 students. The research instruments included: lesson plans and worksheets, PBL implementation sheets, field note formats, process skills observation sheets, and end-of-cycle tests. The study results show that applying the PBL can improve students' critical thinking skills at MAN 2 Indragiri Hilir. The analysis results show an increase in critical thinking aspects. Namely, in the first cycle, the average value is 80.80 with good criteria, and the second cycle has an average value of 93.00 with very good criteria.